2012
DOI: 10.4236/jct.2012.326120
|View full text |Cite
|
Sign up to set email alerts
|

sTRAIL Serum Levels and TRAIL 1595 Genotypes: Associations with Progress and Prognosis of Colorectal Carcinoma

Abstract: Programmed cell death called apoptosis, plays an important role in the development and maintenance of tissue homeostasis and abnormalities in apoptotic function have been known as important events in the pathogenesis of many cancer types, such as colorectal cancer. It has been shown that both the membrane-bound TRAIL and sTRAIL can induce apoptosis in several tumor types by activating death receptors. Our study was to investigate the existence of TRAIL 1595 C/T SNP in colorectal cancer patients and possible ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…In our study, although not statistically significant, the C1595T CT + TT genotype and T allele frequency were lower in stage III and IV NSCLC patients than that of found in stage I and II patients (frequencies of CT+ TT genotype: 29.4% and 39.2%, T allele: 26.5% and 39.2%, respectively), and our results are inconsistent with the results of Luo et al When we approach this issue as general carcinogenesis, Wang et al found that the frequency of TRAIL C1595T variant T carriage in patients with poorly differentiated gastric adenocarcinoma was significantly lower [20]. Yaylım et al found that TRAIL C1595T CC and homozygous CC + TT genotypes frequency were significantly higher in patients with advanced stage tumors of colorectal cancer than in patients with early stage tumors [12]. Yildiz et al detected TRAIL C1595T CT genotype at a significantly lower frequency in patients with advanced stage tumor than those with early stage tumor in breast cancer [13].…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…In our study, although not statistically significant, the C1595T CT + TT genotype and T allele frequency were lower in stage III and IV NSCLC patients than that of found in stage I and II patients (frequencies of CT+ TT genotype: 29.4% and 39.2%, T allele: 26.5% and 39.2%, respectively), and our results are inconsistent with the results of Luo et al When we approach this issue as general carcinogenesis, Wang et al found that the frequency of TRAIL C1595T variant T carriage in patients with poorly differentiated gastric adenocarcinoma was significantly lower [20]. Yaylım et al found that TRAIL C1595T CC and homozygous CC + TT genotypes frequency were significantly higher in patients with advanced stage tumors of colorectal cancer than in patients with early stage tumors [12]. Yildiz et al detected TRAIL C1595T CT genotype at a significantly lower frequency in patients with advanced stage tumor than those with early stage tumor in breast cancer [13].…”
Section: Discussioncontrasting
confidence: 79%
“…Timirci-Kahraman et al found that the frequency of TRAIL 1595 TT genotype was lower in bladder cancer patients than in healthy controls, and the frequency of CT genotype was significantly higher [21]. Yaylım et al in patients with colorectal cancer [12] and Yıldız et al in patients with breast cancer [13] did not find any significant difference in TRAIL C1595T genotype distribution. In our study, we have considered the frequency of this genotype and alleles in Turkish cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations